2017
DOI: 10.1111/apel.12186
|View full text |Cite
|
Sign up to set email alerts
|

TBT and SPS impacts on Korean exports to China: empirical analysis using the PPML method

Abstract: Since diplomatic relations were established between China and Korea, the two countries have expanded their relationships, especially in trading commodities and services. However, in recent years, as tariff levels have fallen, China has sought to implement other protectionist mechanisms. The use of non-tariff measures has added another dimension to international trade activities that need to be better understood. The paper analyses the impacts that two forms of non-tariff measures, technical barriers to trade (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…With several studies emerging that have a key role in helping model [12]) and measure [6]) the impacts of non-tariff measures. There are of course a myriad of other related studies, which have helped to improve our understanding of these forms of policy initiatives [8,9]). An assessment of the literature shows that our understanding of non-tariff instruments has evolved significantly over time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…With several studies emerging that have a key role in helping model [12]) and measure [6]) the impacts of non-tariff measures. There are of course a myriad of other related studies, which have helped to improve our understanding of these forms of policy initiatives [8,9]). An assessment of the literature shows that our understanding of non-tariff instruments has evolved significantly over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Part of this assessment has had various methodological approaches adopted, ranging from large econometric studies using panel and cross sectional data [13]), large computable general equilibrium models [14]) or sector-or policy-specific econometric studies [15]). Moreover, from an empirical perspective, different proxies have been used to measure NTMs such as frequency indexes and coverage ratios [8,9,16], which have shown mixed results as to the impact the measures have on trade flows. While the findings tend to be negative if NTMs are proxied by ad-valorem equivalent (AVE) [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we performed PPML as suggested by Silva & Tenreyno (2006) to examine the effect of key macro-economic variables on the export of Indonesian canned tuna from the last 10 years. The applications of this method to the analysis of international trade have been carried out by Wei, Huang & Jun (2012), Ehrich & Mangelsdorf (2018), Wood, Wu, Li, & Kim (2017), Jayasinghe, Beghin, & Moschini (2010), Bojnec & Fert (2015), and Braha, Qineti, Cupák, & Lazor áková (2017). However, most of the empirical applications were applied to food commodities, while the applications in fisheries commodities are still limited.…”
Section: Introductionmentioning
confidence: 99%